Perception on occupational safety and health management and factors contributing to safety satisfaction and feedback among hospital staff nurses in Sabah state health department - Nelbon, Giloi (Universiti Malaysia Sarawak (UNIMAS), 2010)
ThiS study examined the perception of employees regarding Occupational Safety and Health (OSH) Management and factors contributing to safety satisfaction and feedback among grade U29 hospital staff nurses in the Sabah Health Department. It is a cross-sectional study using a validated self-administered questionnaire which consists of ten independent variables using 5point Likert-type scales. A total of 135 nurses randomly selected from seven government hospitals that responded have participated in the study with a response rate of 63.4~ThiS study reveals that training & competence (4.04 ± 0.65) is perceived as the most important component Xl of their workplace OSH practice followed by safety rules & reporting (3.70 ± 0.63), and work pressure was the least important (2.76 ± 0.48). Safety satisfaction & feedback on safety mean score are 3.28 ± 0.51 and 3.57 ± 0.73 respectively. From a Pearson's correlation analysis result, it indicated that safety communication, safety responsibility training & competence, safety rules and reporting, health safety goal, role of supervisor as well as supervisor's leadership have a significant positive relationship with employee outcome while safety incidents has a negative correlation to it. This is expected as safety incidents are undesired occurrences at workplace. However this relation is not significant. A regression analysis was conducted to examine the relationship between OSH management components and employee outcome. Two components namely safety rules & reporting (Adj. b=0.26, CI 0.13-0.4, p<O.OOI) and work pressure (AdJ b=O.22, CI 0.09-0.34, p=O.OO 1) contributes significantly to the prediction of employee outcome (R2 = 0.29). The overall observation from this study indicated that the perception on OSH management in this population is low. Efforts and new strategies on how to improve OSH management need to be identified and implemented in order to ensure better safety climate in the public hospitals which would eventually improve the quality of service rendered to the population at large.